1992
DOI: 10.1002/aja.1001930403
|View full text |Cite
|
Sign up to set email alerts
|

Effect of systemic calcium deficiency on the expression of transforming growth factor‐β in chick embryonic calvaria

Abstract: The developmental process of intramembranous ossification involves bone formation directly from mesenchymal differentiation without a cartilage intermediate. We have previously observed that systemic calcium deficiency in the developing chick embryo, produced by long-term shell-less culture, results in the appearance of chondrocyte-like cells in the calvarium, a parietal bone which normally develops via intramembranous ossification. This investigation aims to analyze the mechanism underlying this calcium defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
11
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 62 publications
6
11
0
Order By: Relevance
“…Previous studies by several authors [22][23][24], as well as a pilot study from our laboratory, have reported that Ca repletion to the shell-less embryos in the form of two to three 5-6 cm 2 eggshell pieces or a daily addition of CaCO 3 suspension (10% w/v in water), applied as several spots, onto the CAM resulted in improved overall growth and increased calcification of the skeletal components, especially the endochondral long bones (femur and tibia). In the chick embryo, the Ca required for skeletal mineralization is mobilized from the CaCO 3 , in the form of calcite, stored in the eggshell by the CAM [22][23][24].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Previous studies by several authors [22][23][24], as well as a pilot study from our laboratory, have reported that Ca repletion to the shell-less embryos in the form of two to three 5-6 cm 2 eggshell pieces or a daily addition of CaCO 3 suspension (10% w/v in water), applied as several spots, onto the CAM resulted in improved overall growth and increased calcification of the skeletal components, especially the endochondral long bones (femur and tibia). In the chick embryo, the Ca required for skeletal mineralization is mobilized from the CaCO 3 , in the form of calcite, stored in the eggshell by the CAM [22][23][24].…”
Section: Discussionmentioning
confidence: 98%
“…In the chick embryo, the Ca required for skeletal mineralization is mobilized from the CaCO 3 , in the form of calcite, stored in the eggshell by the CAM [22][23][24]. In our experimental model, the scaffold was implanted on the CAM at 10 days of embryonic development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In situ hybridization was performed essentially as described previously (McDonald and Tuan, 1988;Sato and Tuan, 1992). Sections were deparaffinized with xylene followed by Americlear (Polysciences, Warrington, PA) for 20 min each, hydrated through a graded series of ethanol (loo%, 95%, 70%, and 50%) for 1 min each, equilibrated with 2 x SSC for 1 min, and demineralized in 0.25 M HC1 for 30 min.…”
Section: In Situ Hybridizationmentioning
confidence: 99%